Effect of Incorporation of Oats and Malted Barley Flours on the Quality of Cookies - Maskey, Bunty; Paudel, Ashish; Shrestha, Nabindra Kumar (Himalayan Journal of Science and Technology, 2021)
The study aimed to determine the potential of oats and malted barley flours incorporation on cookie making. D-optimal mixture design was employed for formulating the recipe of cookies. Seven different formulations of recipe containing oats flour: malted barley flour: wheat flour in the ratio of 20:25:55, 15:30:55, 13:32:55, 10:35:55, 7:38:55, 5:40:55 and 100:0:0 was prepared. The prepared cookies were subjected to sensory evaluation for consumer acceptability and the data obtained were statistically analyzed using two-way ANOVA (no blocking) at a 5% level of significance. From the mean sensory scores, the formulation 10:35:55 was selected as the optimized formulation and subjected to proximate analysis. The optimized cookies were significantly (p<0.05) superior in the case of protein (7.50%), fat (22.93%), fiber (2.90%), and ash content (0.97%) to wheat cookies (6.43%, 18.83% 0.83% and 0.41% respectively) as seen higher in oats and malted barley flours than wheat flour. The calcium content was found to be significantly (p<0.05) higher in optimized cookies (35.3 mg/100g) than wheat cookies (18.40 mg/).